The Role of Internet Usage in Shaping the Relationship between Consumer Tendencies and Life Satisfaction among Gen Z in Malaysia - Faiz, Masnan; SITI BALKIS, MOHAMED IBRAHIM; Mohd Shahidan, Shaari (Universiti Kebangsaan Malaysia Press, 2025)
This study investigates the psychological and behavioural factors influencing life satisfaction among Generation Z, focusing on the roles of fear of missing out (FOMO), novelty seeking, and sale proneness as predictors, with impulse buying as a mediating variable and internet use as a moderator. Using a detailed quantitative approach and data analysed via SPSS and SmartPLS, the results reveal that both FOMO and novelty seeking significantly influence impulse buying, while sale proneness directly enhances life satisfaction. Furthermore, internet use significantly moderates the relationship between novelty seeking and impulse buying, intensifying impulsive behaviour in digital contexts. These findings contribute to the theoretical understanding of digital consumer behaviour, while providing practical insights for marketers and digital platforms to design ethically responsible and targeted strategies. Limitations and future research directions are also discussed to extend the scope of inquiry across generational and cultural contexts, highlighting the need for future research using longitudinal methods and broader age groups to better understand the digital era consumer’s behaviour and their life satisfaction. Moreover, future studies should also incorporate additional psychological constructs such as emotional regulation, financial literacy, peer influence, and digital fatigue to provide a more comprehensive model of consumer behaviour life satisfaction.